Defunctioning polymorphism in the immunoglobulin G inhibitory receptor (FcγRIIB-T/T232) does not impact on kidney transplant or recipient survival - Clatworthy, Menna R.; Matthews, Rebeccah J.; Doehler, Bernd; Willcocks, Lisa C.; Opelz, Gerhard; Smith, Kenneth G. C. (Transplantation, 2014)
Background - There is an increasing appreciation of the deleterious effects of antibody and B cells on acute and chronic transplant outcomes. Many effector functions of antibody are mediated by a family of receptors (FcγRs) that are expressed on most immune cells, including neutrophils, natural killer cells, and B cells. Most FcγRs are activating and controlled by a single inhibitory receptor, FcγRIIB (CD32B), which also regulates some aspects of B-cell activation and antibody production. FcγRIIB-deficient mice develop severe chronic arteriopathy in a murine cardiac allograft model. A single nucleotide polymorphism in human FcγRIIB (rs1050501) results in profound receptor dysfunction and is associated with systemic lupus erythematosus. The frequency of this FcγRIIB-I/T232 polymorphism also shows significant racial variation. - Methods - In the present study, we sought to determine whether the FcγRIIB-I/T232 single nucleotide polymorphism rs1050501 affected susceptibility to renal allograft rejection or loss and transplant recipient survival. FcγRIIB-I/T232 genotype was determined in 2,851 Caucasian and 570 Afro-Caribbean renal transplant recipients, and in 236 transplant recipients with a primary diagnosis of systemic lupus erythematosus, all of whom were enrolled into the Collaborative Transplant Study. - Results - We found no significant difference in pretransplant panel reactive antibodies, acute rejection at 1-year nor in 10-year transplant or patient survival in individuals with differing FcγRIIB-I/T232 genotype. - Conclusion - This negative result is surprising, given the importance of this receptor in modulating antibody effector function.